Phyto-rhizoremediation potential of C. zizanioides augmented with Bacillus infantis (VITVJ8) for the uptake of heavy metals (Cr, Pb and Zn) - Vaishnavi, Jeevanandam; Osborne W., Jabez (Frontiers in Soil Science, 2025)
The accumulation of heavy metals in the ecosystem due to industrialization has led to toxic effects on various life forms such as flora, fauna and microfauna. Several approaches that are currently used for the removal of heavy metals are not cost-effective and efficient. Therefore, the current study was focused on the bio-removal of chromium (Cr), lead (Pb) and zinc (Zn) using augmentation with strong biofilm forming Bacillus infantis (VITVJ8), which was confirmed by Bacillus infantis augmented to the rhizosphere region of Chrysopogon zizanioides with a percentage of 0.025%. The bioremoval process was catalyzed by superoxide dismutase, chromate reductase and catalase activity with 83U/ml, 51U/ml and 75U/ml, respectively. VITVJ8 was also found to be a plant growth promoting bacterium as it was capable of producing indole acetic acid (IAA) 63µg/ml and siderophores 1.238cm and of solubilizing insoluble phosphate 72.3%. The bacterium could tolerate Cr and Zn up to 1000ppm, whereas for Pb it was 1250ppm. Further, rhizoremediation setup consisting of C. zizanioides augmented with VITVJ8 strain showed enhanced uptake of Zn, Pb and Cr (89% > 86% > 77%) as compared to phytoremediation (60% > 62% > 59%) treated plants. Seed germination assay revealed 75.78% increase in the germination index for set-ups treated with B. infantis, which also confirmed the reduction in heavy metal (HM) toxicity upon treatment with effective strain and enhanced plant growth. Since the uptake was found to be maximum in the roots versus the shoots, vetiver can be considered as a root accumulator of Cr, Pb and Zn when amended with B. infantis.